Website development on herbal plant diversity as media in Kurikulum Merdeka - Ariftania Madrin; R. Ratnawati (University of Muhammadiyah Malang, 2024)
Local wisdom which is the theme of the project to strengthen the character of Pancasila in the Merdeka Curriculum includes the fading of ancestral culture such as traditional vegetable medicine. Although schools have limited resources for teaching local wisdom through books, students' preference for mobile learning requires a more flexible and practical approach, as seen from the use of Tambakboyo Reservoir's herbal diversity as website content. This research aims to determine the types of herbal plants in the Tambakboyo Reservoir and their suitability as learning media. This R&D research uses the ADDIE model which is limited to the development stage. There are 62 types of Indonesian herbal plants in Tambakboyo Reservoir. The results of reviews by material experts, media experts, practitioners, and student readability tests on the herbal plants website show that the media is declared appropriate and meets the assessment criteria and can then be continued with implementation.